An update on the roles of circular RNAs in osteosarcoma. (25th October 2020) - Li, Zheng; Li, Xingye; Xu, Derong; Chen, Xin; Li, Shugang; Zhang, Lin; Chan, Matthew T. V.; Wu, William K. K.
Abstract: Osteosarcoma is the most common primary bone malignancy and is a neoplasm thought to be derived from the bone‐forming mesenchymal stem cells. Aberrant activation of oncogenes and inactivation of tumour suppressor genes by somatic mutations and epigenetic mechanisms play a pivotal pathogenic role in osteosarcoma. Aside from alterations in these protein‐coding genes, it has now been realized that dysregulation of non‐coding RNAs (ncRNAs), including microRNAs (miRNAs), long non‐coding RNAs (lncRNAs) and the recently discovered circular RNAs (circRNAs), is crucial to the initiation and progression of osteosarcoma. CircRNAs are single‐stranded RNAs that form covalently closed loops and function as an important regulatory element of the genome through multiple machineries. Recently, an increasing number of studies suggested that circRNAs also played critical roles in osteosarcoma. This review summarizes recent development and progression in circRNA transcriptome analysis and their functions in the modulation of osteosarcoma progression. Abstract : The representative diagram of circRNA mediated ceRNA network and oncogene signaling pathways. The current study in osteosarcoma highlights the regulatory relationship of the circRNA‐miRNA‐mRNA network for different signaling pathways. Multiple identified circRNAs function as miRNA sponge and subsequently upregulate relevant target genes expression level.